Latar Sosial Pembentuk Karakter Tokoh Utama Dalam Novel Selena Karya Tere Liye - Putri, Widuri Salena; Hakim, Man; Lisdayanti, Septina; Yuniati, Ira (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The characters in the novel are generally not formed just like that, but are born from interactions with the social environment that surrounds them. Their characters are a reflection of the social background in which they grow and develop. This study aims to determine the influence of social background on the formation of the character of the main character in the novel Selena by Tere Liye. This study uses a qualitative descriptive method. The data in this study are in the form of quotes that describe the character and social background of the main character. The data source is the novel Selena by Tere Liye. The data collection technique in this study is a literature study, the data analysis technique uses a structural approach. The results of the research conducted, the main protagonist in the novel Selena is Selena, found 13 characters in the character of Selena based on the character of the main protagonist which is dominated by the character of a hard worker, responsible, socially concerned, honest, independent, disciplined, creative, friendly, diligent, tolerant, curious, appreciating achievement and calm. Researchers found 8 aspects of 9 categories of social background in the novel including social status, occupation, education, economy, social norms and values, lifestyle, social relationships, inequality/social conflict. Based on the 8 aspects of social background contained in Tere Liye's novel Selena, 6 of them influence the formation of Selena's character, namely Work, Education, Economy, Social Norms and Values, Social Relations, and Social Inequality/Conflict